The Value Relevance of Accounting and Financial Information in Stock Returns: The Case of Jordanian Commercial Banks - Mohammad Jadallah, Oroba; Salim Haddad, Fayez; Hussein Al Tarawneh, Ahmad (Jordan Journal of Business Administration, 2023)
The primary aim of this research is to examine the value relevance of accounting and financial information in explaining stock returns by using panel data for a sample of 13 commercial banks listed in Amman Stock Exchange (ASE), through the period from 2010 to 2018. It uses dividends payout ratio, book value per share and earnings per share as proxies of accounting and financial information. The findings indicate that earnings per share, book value per share, dividends payout ratio and bank size do not influence stock returns. These results are consistent with Black and Scholes (1974) and Fama and French (1992), among others.